Global Climate Change : Market-Based Strategies to Reduce Greenhouse Gases. (U.S. Congressional Research., 2003)
Provides background on global climate change, international response, and cost estimates of control schemes; and examines market-based mechanisms for reducing greenhouse gases, including tradeable permits (allowances and credits) and a carbon dioxide emissions tax. Discusses joint implementation and issues related to greenhouse gas reduction efforts; and reviews 108th Congress legislation and Administration initiatives.